Copper sulfide and silver sulfide thin films prepared by solid-vapor reactions - Ortíz Díaz, M. (OMICS international, 2019)
Currently, copper sulphide and silver sulphide thin films have been received a lot of attention from researcher. These films could be used for electronic, photonics, optoelectronic devices, solar cells, solar selective coatings, resistive switches, filament memories, and infrared detectors. Because of they have very unique properties (optical electrical, photocatalytical and photovoltaic properties), low cost and no toxicity. In this work, nanostructured copper sulphide and silver sulphide films were synthesized by using solid vapor reactions. Advantages and basic principles of this technique were discussed.